New species and records of Entomobryidae and Orchesellidae (Collembola) from the East Caucasus (Russia) - Baquero, Enrique; Potapov, Mikhail; Jordana, Rafael (Zootaxa, 2021)
We studied Entomobryidae and Orchesellidae springtails collected throughout Chechnya, Ingushetia, and Dagestan, Russia. Three new species of the genus Entomobrya (E. multisetis sp. nov., E. hirsutothorax sp. nov., and E. kremenitsai sp. nov.), and one of Entomobryoides (E. dagestanicus sp. nov.) are described. Taxonomic information for Entomobrya nicoleti (Lubbock, 1868), Willowsia potapovi Zhang et al., 2011, and Heteromurus nitidus (Templeton, 1836) in Templeton & Westwood 1836 from the Caucasus are given.